A Deep Learning Approach to the Malware Classification Problem using Autoencoders - Pinto, Dhiego Ramos; Duarte, Julio Cesar; Sant’Ana, Ricardo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Detecting malicious code or categorizing it among families has become an increasingly difficult task. Malware1 exploits vulnerabilities and employ sophisticated techniques to avoid their detection and further classification, challenging cybersecurity teams, governments, enterprises, and the ordinary user, causing uncountable losses annually.